Carbon Tax in Indonesia: Challenges and Opportunities - Fatma Ayu Husnasari (Business and Human Rights Law & Policy, 2025)
In order to control GHG emissions to support NDCs achievement, the government imposes a carbon tax. A carbon tax is an instrument which puts a price on the carbon released from the use of fossil fuels, namely oil, natural gas, and coal. This carbon tax is implemented to change industrial behaviour, as industries are encouraged to avoid this additional charge. Thus, it helps shift industries to green economic activities with low carbon emission. This paper will explore further regarding carbon tax in Indonesia addressing two questions: how is the laws of carbon tax in Indonesia? and what are carbon tax challenges and opportunities in the country? This paper consists of seven sections. The first section will present the background of carbon tax as a part of climate change initiatives in Indonesia. The second section will cover the development of carbon tax law in the country. The third section will present carbon tax in the international aspect. The fourth section will discuss further some challenges and opportunities of carbon tax in Indonesia. The fifth section will provide some highlights as a comparison in implementing carbon tax water in other countries. The final section will review the progress of implementation of carbon tax laws in Indonesia.